Establishing a Community of Practice for Doctoral Studies Amidst the COVID-19 Pandemic (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
In this discussion paper, we describe our experience completing the first year of the doctorate in nursing program at a large urban academic centre during the COVID-19 pandemic. We highlight the current nursing shortage and the importance of supporting all nursing students, including nurses in doctoral programs, towards successful graduation. We describe the development of a virtual community of practice incorporating five key strategies: building community, fostering collaboration, strengthening connection, enhancing creativity, and promoting consistency. We believe that utilizing these strategies will contribute to our success and may be relevant to nursing leaders seeking to support the development of more doctorally prepared nurses. Participation in a community of practice early on in doctoral education will not only better prepare students for success in their program, but also continued success as they progress through their careers. It is important for students to not only make connections with peers in their area of academic study, but to also reach out to peers in other disciplines to improve both individual and interdisciplinary growth. Program administrators and educators can encourage the formation of community of practice among novice doctoral students. This encouragement can be achieved using a virtual platform, or in-person networking opportunities. Inviting incoming graduate students to connect with each other and with students from previous cohorts also fosters community of practice formation.